Building peace and development : 1994 : report on the work of the organisation from the 48th to the 49th Session of the General Assembly - Boutros-Ghali, Boutros (UN New YorkUS, 1994)
Describes the work of the UN over the period September 1993 to September 1994. Deals with both the economic and social questions of development as well as the UN's peace-keeping operations.